2018
DOI: 10.1111/gcb.14276
|View full text |Cite
|
Sign up to set email alerts
|

Plant cuticle under global change: Biophysical implications

Abstract: Climatic stressors due to global change induce important modifications to the chemical composition of plant cuticles and their biophysical properties. In particular, plant cuticles can become heavier, stiffer and more inert, improving plant protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
1
21
0
2
Order By: Relevance
“…The pericarp is covered by a layer of cuticle that is composed of two major components including cutin and cuticular waxes (Benítez et al., 2019; Zhao et al., 2019). Plant cuticles perform diverse biological functions, such as regulation of gas exchange, interaction with pathogens and insects, and protection against different abiotic and biotic stresses (Heredia‐Guerrero et al., 2018). The present results by SEM observations showed that the coverage of wax on the areca nut skin decomposed gradually with the extension of storage time.…”
Section: Discussionmentioning
confidence: 99%
“…The pericarp is covered by a layer of cuticle that is composed of two major components including cutin and cuticular waxes (Benítez et al., 2019; Zhao et al., 2019). Plant cuticles perform diverse biological functions, such as regulation of gas exchange, interaction with pathogens and insects, and protection against different abiotic and biotic stresses (Heredia‐Guerrero et al., 2018). The present results by SEM observations showed that the coverage of wax on the areca nut skin decomposed gradually with the extension of storage time.…”
Section: Discussionmentioning
confidence: 99%
“…Huth and colleagues mechanically removed the epicuticular waxes found on the surface of Eucalyptus leaves and used AFM to show those structures are capable to regenerate their original morphology—interestingly the process work regardless of leaf age ( Huth et al., 2018 ). Environmental factors associated with global warming, such as temperature increases, and frequent droughts can significantly modify the composition and properties of the cuticle (reviewed in Heredia-Guerrero et al., 2018 ; Suseela and Tharayil, 2018 ). Those modifications are thought to improve plants protection and their ability to buffer the impact of climate change, and it will be important for future studies to investigate how these affect the topography of the cuticle.…”
Section: Combining Physics Chemistry and Mathematics To Understand Pattern Formation And Propertiesmentioning
confidence: 99%
“…Fruit cuticle analyses have been carried out in a significant number of crops. The cuticle has been shown to respond to environmental changes modifying its quantitative and qualitative composition together with its biophysical performance (Heredia-Guerrero et al, 2018). Nevertheless, exploration of different cultivars, varieties, naturally occurring mutants, related wild-species as well as segregant and mutagenized populations has uncovered a significant degree of variability in cuticle thickness, amount, chemical composition, biophysical properties, etc.…”
Section: The Fruit Cuticlementioning
confidence: 99%